2008
DOI: 10.1002/jbm.a.31990
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced in situ formation of various F‐actin assemblies with a photoresponsive polycation

Abstract: We developed a novel in situ method for the control of F-actin assembly by using a synthetic photoresponsive polycation. The photoresponsive polycation mainly comprises a water-soluble cationic monomer and also contains a small amount of the monomer of a triphenylmethane leucohydroxide derivative (20 mol %), which is a well-known photochromic molecule that can be cationized in aqueous solution by ultra violet (UV) irradiation, thereby causing an increase in the total charge on the photoresponsive polycation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…To date, many studies on the actin organization have been reported to elucidate the cellular mechanism. However, limited attempts have been made to investigate the effect of spatial distribution of binding proteins or polycations on the actin organization . As a future study, we will investigate the effect of spatial distribution of polycations on the morphological transformation of the actin-encapsulated liposome by applying local UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…To date, many studies on the actin organization have been reported to elucidate the cellular mechanism. However, limited attempts have been made to investigate the effect of spatial distribution of binding proteins or polycations on the actin organization . As a future study, we will investigate the effect of spatial distribution of polycations on the morphological transformation of the actin-encapsulated liposome by applying local UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…This appears to be mediated through an inhibition of p47 phox translocation leading to a reduction in NADPH oxidase activity and to a diminution in neutrophil degranulation. Upon stimulation, neutrophils undergo a series of structural and functional rearrangements to enable the killing of ingested microbes, which is made possible by the conversion of G-actin to F-actin in order to facilitate the internal rearrangements (Misu et al, 2009). This work demonstrates that fumagillin may act by retarding the conversion of G to F actin and as a consequence this could hinder the other structural alterations associated with neutrophil activation.…”
Section: Utmentioning
confidence: 87%
“…A temporal control on the self‐assembly process of a motor protein system has been achieved through a novel in situ method, by combining a ‘top down’ and ‘bottom up’ approach. For this, a synthetic photoresponsive polycation has been developed, which provided a means for spatiotemporal control over polymer/actin complex formation 77. The photoresponsive polycation was mainly comprised of a water soluble cationic monomer and also contained a small amount of monomer of a triphenylmethane leucohydroxide derivative, a well known photochromic molecule that can be cationized in aqueous solution by UV irradiation, thereby causing an increase in the total charge on the photoresponsive polycation.…”
Section: Self‐organization and The Bottom‐up Approachmentioning
confidence: 99%